Precalculus: Mathematics for Calculus, 7th Edition

Published by Brooks Cole
ISBN 10: 1305071751
ISBN 13: 978-1-30507-175-9

Chapter 1 - Section 1.3 - Algebraic Expressions - 1.3 Exercises: 88

Answer

$18x^{3}+9x^{2}+2x+1=(9x^{2}+1)(2x+1)$

Work Step by Step

$18x^{3}+9x^{2}+2x+1$ Group the first two terms together. Do the same with the last two terms: $18x^{3}+9x^{2}+2x+1=(18x^{3}+9x^{2})+(2x+1)=...$ Take out common factor $9x^{2}$ from the first parentheses: $...=9x^{2}(2x+1)+(2x+1)=...$ Take out common factor $(2x+1)$: $...=(9x^{2}+1)(2x+1)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.